Association of cyclophilins and cardiovascular risk factors in coronary artery disease - Gegunde, Sandra; Alfonso, Amparo; Alvariño, Rebeca; Pérez-Fuentes, Nadia; Bayón-Lorenzo, Jeremías; Alonso, Eva; Ocaranza-Sánchez, Raymundo; Abellás-Sequeiros, Rosa Alba; Santás-Álvarez, Melisa; Vieytes, Mercedes R.; Juanatey-González, Carlos; Botana, Luis M. (Frontiers in Physiology, 2023)
Cyclophilins are chaperone proteins that play important roles in signal transduction. Among them, cyclophilins A, B, C, and D were widely associated with inflammation and cardiovascular diseases. Cyclophilins A and C have been proposed as coronary artery disease biomarkers. However, less is known about their relationship with cardiovascular risk factors. Therefore, this study aimed to determine the association between cyclophilin A, B, C, and D and cardiovascular risk factors in coronary artery disease. Serum levels of cyclophilins were measured in 167 subjects (subdivided according to cardiovascular risk factors presence). This study reveals that cyclophilin A and C are elevated in patients regardless of the risk factors presence. Moreover, cyclophilin B is elevated in male patients with hypertension, type 2 diabetes, or high glucose levels. In addition, cyclophilins A, B, and C were significantly correlated with cardiovascular risk factors, but only cyclophilin B was associated with type 2 diabetes. The multivariate analysis strengthens the predictive value for coronary artery disease presence of cyclophilin A (>8.2 ng/mL) and cyclophilin C (>17.5 pg/mL) along with the cardiovascular risk factors tobacco, hypertension, dyslipidemia, and high glucose and cholesterol levels. Moreover, the risk of coronary artery disease is increased in presence of cyclophilin B levels above 63.26 pg/mL and with hypertension or dyslipidemia in male patients. Consequently, cyclophilins A and C serum levels are reinforced as useful coronary artery disease biomarkers, meanwhile, cyclophilin B is a valuable biomarker in the male population when patients are also suffering from hypertension or dyslipidemia.